Sororidade na educação: uma experiência com oficina de empoderamento feminino - Martins, Lorena Gabriela Santos (2019)
In the context of the feminist movement, sorority emerges, a word that gives name to the feminine union based on empathy and established as a way of fighting the oppressions of a patriarchal society. In order to unite sorority and education, the present work presents the path developed in the structuring of a feminine empowerment workshop, understood here as an educomunicative project. The activity brought together students from the ninth year of a public elementary school of Uberlândia and had discussions on topics such as the difficulties due to male chauvinist, the importance of the feminist movement, the myth of the female rivalry and the sorority, making possible, from the discussions, senses about sorority were shared.